THE ROLE OF THE GUT MICROBIOTA IN NUTRITION AND HEALTH - Payzullaeva Umida Furkat kizi; Ziyadullaev Shukhrat Khudojberdievich (Scholar Express Journals, 2022)
The microbiome refers to the collective genomes of microorganisms in a particular environment, and the microbiota is the community of microorganisms themselves. Approximately 100 trillion microorganisms (most of them bacteria, but also viruses, fungi, and protozoa) exist in the human gastrointestinal tract-the microbiome is now best viewed as a virtual body organ. The human genome consists of approximately 23,000 genes, while the microbiome encodes more than three million genes, producing thousands of metabolites that replace many host functions and therefore affect host fitness, phenotype and health
Keywords: Gut microbiota; antibiotics and pesticides